Distraction histogenesis of the maxillofacial region - Gülses, Aydin; Sencimen, Metin; Ayna, Mustafa; Gierloff, Matthias; Açil, Yahya (Oral and maxillofacial surgery, 2015)
The changes in the surrounding soft tissues during long bone distraction in orthopedic surgery have been the subject of several reports, studies on changes in the craniofacial region, in which various tissues, including the skin, muscle, tendon, blood vessel, and gingiva are rare. Therefore, there is a need for studies on the soft tissue aspects of bone lengthening of the craniofacial region. The aim of this review was to address this issue by reviewing the literature about the distraction histogenesis of various tissues, including skin, muscle, blood vessel, nerve, and gingiva.